Assessment of Occupant Adaptive Heating Behaviour in Office Buildings - A Pilot Field Study. Issue 2 (1st November 2022) - Andrade, I; Krumdieck, S; Becker, S
Abstract: Buildings are responsible for 39% of total global CO2 emissions worldwide, with 33% of energy consumption attributed to space heating in commercial buildings. Adaptive Heating Behaviour (AHB) of office users has a direct impact on energy use and depends on building characteristics which determine the heating load. This pilot field study focuses on the assessment of the AHB of office users of a recently retrofitted university building in Christchurch, New Zealand. AHB was reported by users during three consecutive days with a total heating degree days (HDD at 18°C) of 26.8. Indoor temperature and relative humidity were monitored during the study, and a qualitative analysis was performed to understand occupants' behavioural patterns to maintain or recover thermal comfort in office settings. Participants were categorized according to (i) their reported thermal comfort issues at work, (ii) the adaptive responses they took to recover thermal comfort, and (iii) the effectiveness of such actions. The methods used in this pilot study to assess occupant AHB, were informative to future research on how to link environmental conditions to user behaviour in office settings, through the analysis of qualitative and quantitative data. Identifying patterns and triggers for AHB on a per-case basis is necessary, especially as AHB can significantly influence the building energy consumption.